PLACEMENT OF FUNDS IN THE FORM OF SECURITIES AS A FORM OF AGE DEVELOPMENT - Salwa Ainiya Tsabitha; Niken Ayu Puspita; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
. Currently, the times are increasingly advanced, starting from technology, transportation, payments, placement of funds in securities is one of them. Placement of funds in securities is a bank that only acts as a liaison between customers who need funds and customers who have funds. Placement of these funds is only in securities that are not listed on the stock exchange, such as BI certificates. The purpose of this study is to examine the determination of a fund to become securities and also how is the legal relationship between depositors of funds and banks and what are the legal consequences of placing funds in securities as security for wealth. The conclusion of this study is that the role of securities in a bank is inseparable from the role of banks which have a strategic function in implementing national development. The development of the times is also a supporting factor for using securities for payment, deposit of funds, investments, and others. This strategic role is mainly due to the main function of the bank as a vehicle that can collect and distribute public funds effectively and efficiently and anticipate economic and banking developments. To anticipate economic and banking developments as mentioned above, it is necessary to have laws and regulations regarding securities in general that are more adequate as an umbrella that underlies these developments.